Infrastructural nature : five-elements park - Roca, Estanislau, (Iniciativa Digital Politécnica. Oficina de Publicaciones Académicas Digitales de la UPC, 2019)
"Continuity and connectivity, transversality and linearity, permeability and porosity are the urban concepts that we took into account to understand and design within the Zhabei district in order to propose a project that suits the ideas of a well-networked, inclusive and sustainable city".